Subcutaneous versus intravenous administration of Trastuzumab: a minimization cost analysis with real world data from a reference cancer centre in Peru - Otoya, I (2024)
Breast cancer (BC) is a global concern, with Peru experiencing a high incidence and mortality. Trastuzumab, a crucial treatment for human epidermal growth factor receptor 2-positive BC, is administered intravenously or subcutaneously (SC). This study evaluates the costs associated with both methods at Peru's Instituto Nacional de Enfermedades Neoplásicas. Real data indicate that SC administration reduces treatment costs by approximately S/15,049.09. Cross-continental comparisons highlight a global trend favouring SC administration for efficiency and cost-effectiveness. The analysis provides insights for informed decision-making in resource-constrained healthcare settings like Peru, emphasising the need to consider local contexts in optimising oncology care.